A method for preparing environmentally friendly, colorless, transparent, durable flame-retardant coated cotton fabric
By alternately organizing the cotton fabric with sodium alginate and chitosan, a durable, colorless and transparent flame retardant coating is formed, which solves the durability and environmental protection problems of improving the flame retardant performance of cotton fabrics in the prior art, and achieves an efficient and environmentally friendly flame retardant effect.
Patent Information
- Application Number
- CN202411472349.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-10-22
AI Technical Summary
While improving the flame retardant performance of cotton fabrics, the prior art has problems such as poor durability, color influence and complicated process steps, especially the requirements for environmental protection and practical application value have not been met.
The cotton fabric is sorted by alternately using finishing solution 1 and finishing solution 2 to form a circulation mode of "finishing solution 1-finishing solution 2". Finishing solution 1 contains sodium alginate, butane 2-phosphate-1,2,4-tricarboxylate and sodium hypophosphite, and Finishing solution 2 contains chitosan and water. Through covalent bond cross-linking reaction and ionic bond bonding, a durable, colorless and transparent flame retardant coating is formed.
It has achieved the improvement of efficient flame retardant performance of cotton fabrics, the coating is colorless and transparent, and does not affect the color of the fabric. It has good washing resistance and environmental protection advantages.
Smart Images

Figure CN118979386B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of flame-retardant fabrics, and in particular relates to a method for preparing an environmentally friendly, colorless, transparent and durable flame-retardant coated cotton fabric. Background Art
[0002] Cotton fabrics have the advantages of being breathable, comfortable to wear, etc., and are widely used in clothing, interior decoration, bedding and other fields; however, cotton fabrics are extremely flammable and are flammable textiles with high fire hazards. Therefore, flame retardant finishing of cotton fabrics is crucial to reduce household fires and fire hazards. However, as people's requirements for functional textiles become higher and higher, it is of great significance to develop an environmentally friendly and sustainable flame retardant finishing system for textiles.
[0003] The layer-by-layer self-assembly technology deposits flame retardants on the surface of fabrics layer by layer through anionic and cationic electrolytes, effectively improving the flame retardant properties of fabrics. This technology has the advantages of high material utilization and low matrix selectivity, and has been widely used in the field of flame retardant finishing of textiles. However, it is worth noting that the layer-by-layer self-assembly technology still has some defects that need to be solved.
[0004] Reference (Application of electrostatic layer-by-layer self-assembly in flame retardant finishing of cotton fabrics [J]. Printing and Dyeing, 2018, 44(7): 40-44.) successfully assembled ammonium polyphosphate and chitosan onto the surface of cotton fabric for flame retardant finishing by using the electrostatic layer-by-layer self-assembly method. After 20 layers of assembly, the flame retardant properties of the cotton fabric were improved. However, the coating could not be combined with the cotton fabric and was only deposited on the surface of the cotton fabric by the ionic bond between the two, and the durability was poor.
[0005] There are still great challenges in preparing durable flame-retardant fabrics by layer-by-layer self-assembly technology using anionic and cationic electrolytes. Chinese invention patent CN117188148A discloses a layer-by-layer assembly preparation method for durable flame-retardant coated polyester / cotton blended fabrics, which uses a layer-by-layer assembly method to deposit polyethyleneimine, ethanolamine phytate and hydroxyl-p-terephthalaldehyde on the polyester / cotton blended fabric pretreated with glutaraldehyde in sequence to prepare a durable flame-retardant coated polyester / cotton blended fabric. However, glutaraldehyde, hydroxyl-p-terephthalaldehyde react with amino-containing polyethyleneimine and ethanolamine phytate to form a Schiff base structure, which causes the fabric to turn yellow severely, affecting the color of the dyed or printed fabric itself, making it impossible to apply it to the flame-retardant modification of colored fabrics such as clothing and home decoration; this method requires 4 steps of assembly as a cycle, and 4 to 6 cycles are required to prepare flame-retardant polyester / cotton blended fabrics, which has complicated steps and seriously limits its practical application value; in addition, glutaraldehyde, hydroxyl-p-terephthalaldehyde and polyethyleneimine are poor in environmental protection and cause great harm to human skin.
[0006] Therefore, it is of great significance to develop an environmentally friendly, colorless, transparent, and durable flame-retardant coating to improve the flame-retardant function of cotton fabrics. Summary of the invention
[0007] The purpose of the invention is to solve the problems existing in the prior art and provide a method for preparing an environmentally friendly, colorless, transparent and durable flame-retardant coated cotton fabric.
[0008] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0009] A method for preparing an environmentally friendly, colorless, transparent, durable flame-retardant coated cotton fabric, wherein the cotton fabric is finished by alternately using a finishing liquid 1 and a finishing liquid 2 to form a "finishing liquid 1-finishing liquid 2" circulation mode;
[0010] The finishing liquid 1 contains sodium alginate, 2-phospho-1,2,4-tricarboxylic acid butane, sodium hypophosphite and water, and the sodium hypophosphite is used as a catalyst;
[0011] Finishing liquid 2 contains chitosan and water;
[0012] The finishing process corresponding to finishing liquid 1 in each cycle is: padding → pre-baking → baking → washing; the finishing process corresponding to finishing liquid 2 in the last cycle is: padding → pre-baking → baking → washing; the finishing process corresponding to finishing liquid 2 in other cycles is: padding → drying → washing; washing helps to remove 2-phospho-1,2,4-tricarboxylic acid butane, sodium alginate, and chitosan that have not participated in the reaction on the surface, which helps to improve the uniformity and durability of the coating; when finishing liquid 2 is used to finish the fabric, baking is only performed in the last cycle. Such a design is conducive to the full reaction of each component and can avoid significant damage to the physical properties of the fabric;
[0013] All baking temperatures are in the range of 140-150°C, which helps the active carboxyl groups of 2-phospho-1,2,4-tricarboxylic acid butane to undergo covalent cross-linking reactions with the hydroxyl groups of sodium alginate and chitosan, and with the hydroxyl groups of cotton fibers, and also helps to generate ionic bonds and supramolecular forces between chitosan and sodium alginate to attract each other.
[0014] As the preferred technical solution:
[0015] In the method for preparing the environmentally friendly, colorless, transparent, durable flame-retardant coated cotton fabric as described above, all baking times range from 3 to 4 minutes.
[0016] In the method for preparing the environmentally friendly, colorless, transparent, durable flame-retardant coated cotton fabric as described above, all pre-baking and drying temperatures are in the range of 70-80° C. and the time range is 2-3 min.
[0017] In the method for preparing an environmentally friendly, colorless, transparent, durable flame-retardant coated cotton fabric as described above, the rolling rate of all padding ranges from 90 to 100%. The higher the rolling rate, the higher the amount of liquid and flame retardant carried by the cotton fabric, and the better the flame retardant effect.
[0018] The method for preparing the environmentally friendly, colorless, transparent, durable flame-retardant coated cotton fabric as described above has a cycle number of 2 to 3.
[0019] In the method for preparing an environmentally friendly, colorless, transparent, durable flame-retardant coated cotton fabric as described above, in the finishing liquid 1, the concentration of sodium alginate is 10-20 g / L, and the high concentration of sodium alginate is conducive to deposition on the surface of the cotton fabric, the concentration of 2-phospho-1,2,4-tricarboxylic acid butane is 30-50 g / L, and the concentration of sodium hypophosphite is 10-20 g / L.
[0020] As described above, in the method for preparing an environmentally friendly, colorless, transparent, durable flame-retardant coated cotton fabric, the concentration of chitosan in the finishing liquid 2 is 10-20 g / L, and the high concentration of chitosan is conducive to deposition on the surface of the cotton fabric; the pH value of the finishing liquid 2 is adjusted and controlled by adding acetic acid thereto, and the pH value of the finishing liquid 2 is 4-5, and such a pH value setting helps to promote the dissolution of chitosan.
[0021] The method for preparing an environmentally friendly, colorless, transparent, durable flame-retardant coated cotton fabric as described above has a limiting oxygen index of not less than 29.7%, a damaged length of not more than 11.9 cm, and a damaged length of not more than 14.2 cm after 40 washes, and has excellent flame retardant properties and water wash resistance.
[0022] Principle of the invention:
[0023] The invention adopts biomass chitosan as a cationic component, biomass sodium alginate as an anionic component, and 2-phosphate-1,2,4-tricarboxylic acid butane as an anionic cross-linking component, and prepares an environmentally friendly, colorless, transparent, durable flame-retardant coated cotton fabric through layer-by-layer self-assembly treatment.
[0024] During the preparation process, the active carboxyl group of 2-phospho-1,2,4-tricarboxylic acid butane undergoes covalent cross-linking reaction with the hydroxyl groups of sodium alginate and chitosan, and also undergoes covalent cross-linking reaction with the hydroxyl groups of cotton fibers, thereby facilitating the grafting of the flame retardant coating onto the cotton fabric through covalent bonds;
[0025] 2-Phosphate-1,2,4-tricarboxylic acid butane can diffuse into the cotton fiber and undergo a cross-linking reaction inside the cotton fiber, thereby further improving the flame retardant efficiency and water washability;
[0026] Chitosan and sodium alginate can combine in various forms. On the one hand, the amino groups of chitosan and the carboxylate groups of sodium alginate can form ionic bonds. This combination causes the two to deposit together on the surface of cotton fabric to form an insoluble coating. On the other hand, the main chain structures of sodium alginate and chitosan are both based on six-membered glucose rings. This similar chemical basis not only allows them to be tightly combined through ionic bonds, but also further attracts each other through supramolecular forces (such as hydrogen bonds, van der Waals forces, etc.), thereby enhancing the strength of the combination between the two.
[0027] In the final flame-retardant coating, the phosphate group of 2-phospho-1,2,4-tricarboxylic acid butane acts as an acid source, the amino group of chitosan acts as a gas source, and the sugar ring of chitosan and sodium alginate acts as a carbon source. Therefore, the flame-retardant coating mainly improves the flame-retardant properties of cotton fabrics through the expansion flame-retardant mechanism, and has a high flame-retardant efficiency. Chitosan and sodium alginate are both biomass materials and are environmentally friendly flame retardants. The flame-retardant coating generated by the combination of the two is colorless and transparent, does not affect the color of cotton fabrics, and has a high practical application value.
[0028] Beneficial effects:
[0029] The flame retardant coated cotton fabric prepared by the present invention has a colorless and transparent flame retardant coating which does not affect the color of the cotton fabric; has high flame retardant efficiency and good flame retardant and water-washing resistance; the chitosan and sodium alginate used in the flame retardant coating are both biomass materials, which have significant environmental advantages. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a comparison diagram of the surface morphologies of the uncoated (before finishing) cotton fabric and the coated (after finishing) cotton fabric of Example 1 of the present invention. DETAILED DESCRIPTION
[0031] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0032] Testing methods for relevant performance indicators:
[0033] Limiting oxygen index: measured by FTT0080 oxygen index meter according to GB / T 5454-1997 standard;
[0034] The damage length is: According to GB / T 5455-2014 standard, the test is carried out using the M233M vertical combustion test machine;
[0035] Damage length after 40 washes: First wash 40 times according to AATCC 61-2013 "Accelerated Test for Color Fastness to Washing for Household and Commercial Use", and then test with M233M vertical burning tester according to GB / T 5455-2014 standard.
[0036] Example 1
[0037] A method for preparing an environmentally friendly, colorless, transparent, durable flame-retardant coated cotton fabric, the specific steps are as follows:
[0038] (1) Prepare the raw materials:
[0039] Finishing liquid 1: the components are sodium alginate, 2-phosphate-1,2,4-tricarboxylic acid butane, sodium hypophosphite and water; the concentration of sodium alginate is 10 g / L, the concentration of 2-phosphate-1,2,4-tricarboxylic acid butane is 30 g / L, and the concentration of sodium hypophosphite is 10 g / L;
[0040] Finishing solution 2: pH value is 4, the components are chitosan, acetic acid and water, and the concentration of chitosan is 10g / L;
[0041] Cotton fabric: without flame retardant finishing (surface morphology such as Figure 1 The uncoated cotton fabric in the figure has a limiting oxygen index of 18.1% and a damaged length of 30 cm.
[0042] (2) Circular arrangement:
[0043] The cotton fabric is finished by using finishing liquid 1 and finishing liquid 2 alternately, specifically:
[0044] (a) Finishing liquid 1 is used to finish cotton fabric, and the process is: padding → pre-baking → baking → washing; wherein the padding rate is 90%, the pre-baking temperature is 70°C, the pre-baking time is 3 minutes, the baking temperature is 140°C, and the baking time is 4 minutes;
[0045] (b) using finishing liquid 2 to finish the cotton fabric, the process is: padding → drying → washing; the padding rate is 90%, the drying temperature is 70°C, and the drying time is 3 min;
[0046] (c) using finishing liquid 1 to finish the cotton fabric, the process is: padding → pre-baking → baking → washing; wherein the padding rate is 90%, the pre-baking temperature is 70° C., the pre-baking time is 3 min, the baking temperature is 140° C., and the baking time is 4 min;
[0047] (d) using finishing liquid 2 to finish the cotton fabric, the process is: padding → pre-baking → baking → washing; wherein the padding rate is 90%, the pre-baking temperature is 70°C, the pre-baking time is 3 minutes, the baking temperature is 140°C, and the baking time is 4 minutes;
[0048] After the above finishing steps are completed, an environmentally friendly, colorless, transparent, durable flame retardant coated cotton fabric (surface morphology such as Figure 1 medium coated cotton fabric shown).
[0049] The environmentally friendly, colorless, transparent, durable flame-retardant coated cotton fabric finally obtained had a limiting oxygen index of 29.7%, a damaged length of 11.9 cm, and a damaged length of 14.2 cm after 40 washes.
[0050] Comparative Example 1
[0051] A method for preparing a flame retardant coated cotton fabric is basically the same as that of Example 1, except that the finishing liquid 1 of this comparative example does not contain 2-phospho-1,2,4-tricarboxylic acid butane, and other conditions remain unchanged.
[0052] The environmentally friendly, colorless, transparent, durable flame-retardant coated cotton fabric finally obtained has a limiting oxygen index of 24.3% and a damaged length of 30 cm. The damaged length after 40 washes is 30 cm.
[0053] Compared with Example 1, the flame retardant effect of the cotton fabric prepared in Comparative Example 1 is significantly reduced. This is because Comparative Example 1 is assembled only with anionic sodium alginate and cationic chitosan, and the flame retardant efficiency of sodium alginate and chitosan alone is low, resulting in poor flame retardant properties of the modified cotton fabric.
[0054] Comparative Example 2
[0055] A method for preparing flame-retardant coated cotton fabric is basically the same as Example 1, except that in the finishing liquid 2 of this comparative example, polyethyleneimine (Chinese medicine code L04052701, Sinopharm Chemical Reagent Co., Ltd.) is used instead of chitosan, and other conditions remain unchanged.
[0056] The environmentally friendly, colorless, transparent, durable flame-retardant coated cotton fabric finally obtained has a limiting oxygen index of 30.3%, a damaged length of 10.5 cm, and a damaged length of 30 cm after 40 washes.
[0057] Compared with Example 1, the flame retardant performance of Comparative Example 2 is slightly improved, but the flame retardant durability is significantly reduced. This is because although the nitrogen content of polyethyleneimine is high, it helps to build a synergistic flame retardant effect to improve the flame retardant performance, but the cationic polyethyleneimine can only form ionic bonds with anionic sodium alginate, and cannot form covalent bonds with 2-phosphate-1,2,4-tricarboxylic acid butane, which leads to poor durability of the flame retardant coated cotton fabric.
[0058] Example 2
[0059] A method for preparing an environmentally friendly, colorless, transparent, durable flame-retardant coated cotton fabric, the specific steps are as follows:
[0060] (1) Prepare the raw materials:
[0061] Finishing liquid 1: the components are sodium alginate, 2-phosphate-1,2,4-tricarboxylic acid butane, sodium hypophosphite and water; the concentration of sodium alginate is 13 g / L, the concentration of 2-phosphate-1,2,4-tricarboxylic acid butane is 40 g / L, and the concentration of sodium hypophosphite is 14 g / L;
[0062] Finishing solution 2: pH value is 4.5, the components are chitosan, acetic acid and water, and the concentration of chitosan is 15g / L;
[0063] Cotton fabric: without flame retardant finishing, limiting oxygen index is 18.1%, and the damaged length is 30cm;
[0064] (2) Circular arrangement:
[0065] The cotton fabric is finished by using finishing liquid 1 and finishing liquid 2 alternately, specifically:
[0066] (a) The cotton fabric was finished using finishing liquid 1, and the process was: padding → pre-baking → baking → washing; wherein the padding rate was 95%, the pre-baking temperature was 74°C, the pre-baking time was 2.5 min, the baking temperature was 145°C, and the baking time was 3.5 min;
[0067] (b) Finishing liquid 2 was used to finish the cotton fabric, and the process was: padding → drying → washing; the padding rate was 95%, the drying temperature was 74°C, and the drying time was 2.5 min;
[0068] (c) using finishing liquid 1 to finish the cotton fabric, the process is: padding → pre-baking → baking → washing; wherein the padding rate is 95%, the pre-baking temperature is 74° C., the pre-baking time is 2.5 min, the baking temperature is 145° C., and the baking time is 3.5 min;
[0069] (d) using finishing liquid 2 to finish the cotton fabric, the process is: padding → pre-baking → baking → washing; wherein the padding rate is 95%, the pre-baking temperature is 74°C, the pre-baking time is 2.5 min, the baking temperature is 145°C, and the baking time is 3.5 min;
[0070] After the above finishing steps are completed, an environmentally friendly, colorless, transparent, durable flame-retardant coated cotton fabric is obtained;
[0071] The environmentally friendly, colorless, transparent, durable flame-retardant coated cotton fabric finally obtained had a limiting oxygen index of 30.5%, a damaged length of 10.8 cm, and a damaged length of 13.8 cm after 40 washes.
[0072] Example 3
[0073] A method for preparing an environmentally friendly, colorless, transparent, durable flame-retardant coated cotton fabric, the specific steps are as follows:
[0074] (1) Prepare the raw materials:
[0075] Finishing liquid 1: the components are sodium alginate, 2-phosphate-1,2,4-tricarboxylic acid butane, sodium hypophosphite and water; the concentration of sodium alginate is 16 g / L, the concentration of 2-phosphate-1,2,4-tricarboxylic acid butane is 45 g / L, and the concentration of sodium hypophosphite is 17 g / L;
[0076] Finishing solution 2: pH value is 5, the components are chitosan, acetic acid and water, and the concentration of chitosan is 17g / L;
[0077] Cotton fabric: without flame retardant finishing, limiting oxygen index is 18.1%, and the damaged length is 30cm;
[0078] (2) Circular arrangement:
[0079] The cotton fabric is finished by using finishing liquid 1 and finishing liquid 2 alternately, specifically:
[0080] (a) Finishing liquid 1 was used to finish the cotton fabric, and the process was: padding → pre-baking → baking → washing; wherein the padding rate was 97%, the pre-baking temperature was 77°C, the pre-baking time was 2.3 min, the baking temperature was 145°C, and the baking time was 3.3 min;
[0081] (b) The cotton fabric was finished using finishing liquid 2, and the process was: padding → drying → washing; the padding rate was 97%, the drying temperature was 77°C, and the drying time was 2.3 min;
[0082] (c) using finishing liquid 1 to finish the cotton fabric, the process is: padding → pre-baking → baking → washing; wherein the padding rate is 97%, the pre-baking temperature is 77°C, the pre-baking time is 2.3 min, the baking temperature is 145°C, and the baking time is 3.3 min;
[0083] (d) The cotton fabric was finished using finishing liquid 2, and the process was: padding → drying → washing; the padding rate was 97%, the drying temperature was 77°C, and the drying time was 2.3 min;
[0084] (e) Finishing the cotton fabric with finishing liquid 1, the process is: padding→prebaking→baking→washing; wherein the padding rate is 97%, the prebaking temperature is 77° C., the prebaking time is 2.3 min, the baking temperature is 145° C., and the baking time is 3.3 min;
[0085] (f) Finishing the cotton fabric with finishing liquid 2, the process is: padding → pre-baking → baking → washing; wherein the padding rate is 97%, the pre-baking temperature is 77° C., the pre-baking time is 2.3 min, the baking temperature is 145° C., and the baking time is 3.3 min;
[0086] After the above finishing steps are completed, an environmentally friendly, colorless, transparent, durable flame-retardant coated cotton fabric is obtained;
[0087] The environmentally friendly, colorless, transparent, durable flame-retardant coated cotton fabric finally obtained had a limiting oxygen index of 31.2%, a damaged length of 10.1 cm, and a damaged length of 13.2 cm after 40 washes.
[0088] Example 4
[0089] A method for preparing an environmentally friendly, colorless, transparent, durable flame-retardant coated cotton fabric, the specific steps are as follows:
[0090] (1) Prepare the raw materials:
[0091] Finishing liquid 1: the components are sodium alginate, 2-phosphate-1,2,4-tricarboxylic acid butane, sodium hypophosphite and water; the concentration of sodium alginate is 20 g / L, the concentration of 2-phosphate-1,2,4-tricarboxylic acid butane is 50 g / L, and the concentration of sodium hypophosphite is 20 g / L;
[0092] Finishing solution 2: pH value is 5, the components are chitosan, acetic acid and water, and the concentration of chitosan is 20g / L;
[0093] Cotton fabric: without flame retardant finishing, limiting oxygen index is 18.1%, and the damaged length is 30cm;
[0094] (2) Circular arrangement:
[0095] The cotton fabric is finished by using finishing liquid 1 and finishing liquid 2 alternately, specifically:
[0096] (a) The cotton fabric was finished using finishing liquid 1, and the process was: padding → pre-baking → baking → washing; wherein the padding rate was 100%, the pre-baking temperature was 80°C, the pre-baking time was 2 min, the baking temperature was 150°C, and the baking time was 3 min;
[0097] (b) using finishing liquid 2 to finish the cotton fabric, the process is: padding → drying → washing; the padding rate is 100%, the drying temperature is 80°C, and the drying time is 2 min;
[0098] (c) using finishing liquid 1 to finish the cotton fabric, the process is: padding → pre-baking → baking → washing; wherein the padding rate is 100%, the pre-baking temperature is 80° C., the pre-baking time is 2 min, the baking temperature is 150° C., and the baking time is 3 min;
[0099] (d) using finishing liquid 2 to finish the cotton fabric, the process is: padding → drying → washing; the padding rate is 100%, the drying temperature is 80°C, and the drying time is 2 min;
[0100] (e) using finishing liquid 1 to finish the cotton fabric, the process is: padding → pre-baking → baking → washing; wherein the padding rate is 100%, the pre-baking temperature is 80° C., the pre-baking time is 2 min, the baking temperature is 150° C., and the baking time is 3 min;
[0101] (f) using finishing liquid 2 to finish the cotton fabric, the process is: padding → pre-baking → baking → washing; wherein the padding rate is 100%, the pre-baking temperature is 80° C., the pre-baking time is 2 min, the baking temperature is 150° C., and the baking time is 3 min;
[0102] After the above finishing steps are completed, an environmentally friendly, colorless, transparent, durable flame-retardant coated cotton fabric is obtained;
[0103] The environmentally friendly, colorless, transparent, durable flame-retardant coated cotton fabric finally obtained had a limiting oxygen index of 31.9%, a damaged length of 9.5 cm, and a damaged length of 12.9 cm after 40 washes.
Claims
1. A method for preparing an environmentally friendly, colorless, transparent, durable flame-retardant coated cotton fabric, characterized in that: The cotton fabric is finished by using the finishing liquid 1 and the finishing liquid 2 alternately, forming a "finishing liquid 1-finishing liquid 2" circulation mode; The finishing liquid 1 contains sodium alginate, 2-phosphate-1,2,4-tricarboxylic acid butane, sodium hypophosphite and water, wherein the concentration of sodium alginate is 10-20 g / L, the concentration of 2-phosphate-1,2,4-tricarboxylic acid butane is 30-50 g / L, and the concentration of sodium hypophosphite is 10-20 g / L; The finishing liquid 2 contains chitosan and water, wherein the concentration of chitosan is 10-20 g / L; The finishing process corresponding to finishing liquid 1 in each cycle is: padding → pre-baking → baking → washing; the finishing process corresponding to finishing liquid 2 in the last cycle is: padding → pre-baking → baking → washing; the finishing process corresponding to finishing liquid 2 in other cycles is: padding → drying → washing; All baking temperatures ranged from 140 to 150°C.
2. The method for preparing an environmentally friendly, colorless, transparent, durable flame-retardant coated cotton fabric according to claim 1, characterized in that: All baking times ranged from 3 to 4 minutes.
3. The method for preparing an environmentally friendly, colorless, transparent, durable flame-retardant coated cotton fabric according to claim 1, characterized in that: All pre-baking and drying temperatures range from 70 to 80°C and the time range is from 2 to 3 minutes.
4. The method for preparing an environmentally friendly, colorless, transparent, durable flame-retardant coated cotton fabric according to claim 1, characterized in that: The rolling ratio for all padding processes ranged from 90 to 100%.
5. The method for preparing an environmentally friendly, colorless, transparent, durable flame-retardant coated cotton fabric according to claim 1, characterized in that: The number of cycles is 2 to 3.
6. The method for preparing an environmentally friendly, colorless, transparent, durable flame-retardant coated cotton fabric according to claim 1, characterized in that: The pH value of the finishing solution 2 is 4-5.
7. A method for preparing an environmentally friendly, colorless, transparent, durable flame-retardant coated cotton fabric according to any one of claims 1 to 6, characterized in that: The limiting oxygen index of the environmentally friendly, colorless, transparent, durable flame-retardant coated cotton fabric is not less than 29.7%, the damaged length is not higher than 11.9 cm, and the damaged length after 40 washes is not higher than 14.2 cm.
Citation Information
Patent Citations
Layer-by-layer assembly preparation method of durable flame-retardant coating polyester / cotton blended fabric
CN117188148A
Phosphorylated chitosan derivative as well as preparation method and application thereof
CN112062876A
Layer-by-layer self-assembly flame-retardant fabric based on full-biomass flame-retardant system and preparation method thereof
CN115198527A